Rádio poste da quadra: a participação dos moradores e as disputas sonoras em uma comunidade em Fortaleza - Ribeiro, Milena de Castro (2016)
This research aims to understand the participatory coexistence and relations between the residents of São Vicente de Paulo community (Quadra) and the radio post Centro de Comunicação Alternativa, located in Aldeota district, in Fortaleza (Ceará). From the participatory research (Brandão, 1984; 2006) as a methodology, it was possible to investigate the history of creation of the post radio, consider about the various forms of participation (Bordenave, 1983) of two groups of residents of Quadra, young Catholics and evangelical women, and understand their relationship within the radio in the living with soundscapes (Schafer, 2011) community. Among the final comments, it was possible to understand that the participation of young women and religious radio was given by mobilizing of their own religious groups. Finally, the course of this research also provided interventional times during the anniversary of the program "Remembering is living" and participation in the radio reform. This search path also made me realize that the intervention has been present since my first contact with Quadra’s community. However at first, research and intervention seemed to be distance. I concluded that the participatory methodologies unite these processes.